Development and Validation of an Interleukin-6 Nomogram to Predict Primary Non-response to Infliximab in Crohn’s Disease Patients - Chen, Yueying; Li, Hanyang; Feng, Qi; Shen, Jun (Frontiers in Pharmacology, 2021)
Background: The primary nonresponse (PNR) rate of Infliximab (IFX) varies from 20% to 46% for the treatment of Crohn’s disease (CD). Detected PNR reduces the improper use of specific treatments. To date, there is hardly any knowledge regarding early markers of PNR. The aim of this study was to evaluate the role of Interleukin-6 (IL-6) as an early predictor of PNR of IFX for the treatment of CD. Methods: We enrolled 322 bio-naïve patients diagnosed with CD from January 2016 to May 2020. Primary response was determined at week 14. Multivariable logistic regression was used to construct prediction models. Area under the curve (AUC), calibration and decision curves analyses (DCA) were assessed in the validation cohort. GEO data were analyzed to identify potential mechanisms of IL-6 in IFX therapy for CD. Results: PNR occurred in 31.06% (100 of 322) patients who were assessable at week 14. IL-6 levels significantly decreased after IFX therapy (P < 0.001). The validation model containing IL-6 presented enhanced discrimination with an AUC of 0.908 and high calibration. Decision curve analysis (DCA) indicated that the model added extra predictive value. GEO data confirmed the IL-6 levels were increased in the PNR group and IL-6-related differently expressed genes (DEGs) were enriched in the inflammatory response. Conclusion: We concluded that IL-6 may be used as a predictive factor to assess the risk of PNR to IFX therapy.